ANALYSIS OF THE DEVELOPMENT OF HOUSING CONSTRUCTION IN UZBEKISTAN (Marketing Journal, 2025)
This article analyzes the current state of housing construction and the housing stock in Uzbekistan, as well as the development trends of the housing sector. Construction volumes and the expansion of the housing stock are considered as key indicators. Spec ial attention is given to state -supported mortgage programs and measures to support the private sector. The article also highlights problems such as rising housing prices, shortages of construction materials, and slow technological development. Recommendat ions are provided to promote the development of the sector.
Keywords: housing construction; housing stock; development trends; mortgage programs; construction materials; state policy; housing prices; innovations; investments; rural and urban infrastructure. 220